2021
DOI: 10.3389/fgene.2020.616998
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Autophagy-Related Gene Prognostic Risk Model Based on TCGA Database in Cervical Cancer

Abstract: Background: Autophagy plays an important role in the development of cancer. However, the prognostic value of autophagy-related genes (ARGs) in cervical cancer (CC) is unclear. The purpose of this study is to construct a survival model for predicting the prognosis of CC patients based on ARG signature.Methods: ARGs were obtained from the Human Autophagy Database and Molecular Signatures Database. The expression profiles of ARGs and clinical data were downloaded from the TCGA database. Differential expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The polymorphism of CHMP4C increased the cancer susceptibility and was imbalanced in many cancers, including lung, ovarian, prostate, and cervical cancers (Lin S. L. et al, 2020). Another study showed that CHMP4C is also an autophagyrelated gene, and its participation in the construction of risk models could effectively predict the prognosis of cervical cancer patients and help develop precise treatment strategies (Shi et al, 2020). Notably, similar to CHMP4C, BAK1 was found to be an apoptosis and pyroptosis-related gene (Cowan et al, 2020;Deo et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The polymorphism of CHMP4C increased the cancer susceptibility and was imbalanced in many cancers, including lung, ovarian, prostate, and cervical cancers (Lin S. L. et al, 2020). Another study showed that CHMP4C is also an autophagyrelated gene, and its participation in the construction of risk models could effectively predict the prognosis of cervical cancer patients and help develop precise treatment strategies (Shi et al, 2020). Notably, similar to CHMP4C, BAK1 was found to be an apoptosis and pyroptosis-related gene (Cowan et al, 2020;Deo et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…These findings indicate that these genes play important roles in the occurrence and metastasis of LUAD. The risk score model was a common method to predict the poor prognosis of cancer patients (21,22). A risk model was constructed through Cox regression analysis and AIC screening.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al [ 49 ] also recently established a cervical cancer prognosis model with three ARGs. The AUC area of this model was 0.678 in the training set and 0.756 in the verification set.…”
Section: Discussionmentioning
confidence: 99%